Reproductive parameters of llambina Potamorhina altamazonica (Characiformes: Curimatidae) in the Ucayali river - Flores-Gómez, Stive (2015)
«Llambina» Potamorhina altamazonica is the second dominant species in the commercial fishery landings in the Ucayali region and of great importance in the regional socio-economics. The aim of this study was to determine the reproductive characteristics of this species. Spawning period, sex ratio, average size at maturity and condition factor were analyzed. The analysis showed that the spawning have synchrony with the increase of water level in the Ucayali river in the transition to high water and in the high water seasons, starting in October, with intense spawning between January and February and completion in March. The sex ratio was significantly favorable to females at most times of the year. The average size at first sexual maturity was estimated at 17.8 cm in females and 18.4 cm in males (total length). The fish showed better somatic condition in the dry season (July to October), which corresponds to the period when the detritus is of better quality. The results show that llambina has a seasonal or periodic strategy of life (r2), and the reproductive cycle is closely related to river hydrological changes.